P173 Reduction in non-elective respiratory-related hospitalizations in patients treated with pirfenidone: pooled analyses from three phase 3 trials of pirfenidone in idiopathic pulmonary fibrosis. (15th November 2016) - Ley, B; Swigris, JJ; Day, B; Stauffer, J; Chou, W; Raimundo, K; Collard, H
Abstract : Rationale: Patients with idiopathic pulmonary fibrosis (IPF) are frequently hospitalised for a variety of reasons. Respiratory-related hospitalizations may occur because of acute exacerbations of IPF, respiratory tract infections, respiratory failure and other causes. Regardless of cause, respiratory-related hospitalizations have been linked to poor outcomes in patients with IPF. We describe the proportion of patients from the three Phase 3 pirfenidone IPF trials with at least one non-elective hospitalisation (all-cause, respiratory-related and non-respiratory-related) over 12 months. Methods: In three Phase 3 randomised, placebo-controlled studies of pirfenidone for IPF (CAPACITY I/II and ASCEND), patients were randomised to pirfenidone (2403 mg/day) or placebo. In the two CAPACITY studies, respiratory-related hospitalizations were a pre-specified endpoint. In ASCEND, hospitalizations were reported as adverse events (AEs), and retrospectively categorised as respiratory-related or non-respiratory by case review. The pooled rates of patients experiencing ≥1 non-elective hospitalizations (all-cause, respiratory-related and non-respiratory-related) for pirfenidone and placebo patients over 12 months are summarised. Rate of death post-hospitalisation was also reported. Results: A total of 1, 247 patients (692 CAPACITY and 555 ASCEND) were included (Table). In pooled analyses, the proportion of patients experiencing ≥1 all-cause hospitalizations over 12 months was no different between pirfenidone and placebo-treated patients. The proportion of patients experiencing ≥1 respiratory-related hospitalizations was 12% in the placebo group vs 7% in the pirfenidone group (odds ratio 0.56; P = 0.004). Deaths after hospitalisation were numerically reduced in the pirfenidone group, most substantially for respiratory-related hospitalizations. Conclusion: Patients with IPF frequently require hospitalisation for a variety of reasons. Pirfenidone may reduce the risk of non-elective respiratory-related hospitalizations over 12 months.